So you may see - Barnas, Muná (Modern Arabic literature., 2011)
This audacious novel opens with Ayn as she reflects on the act of writing and wonders if love alone is sufficient subject for a narrative. Haltingly at first, she weaves the tale of her love affair with Ali with witty asides about her own writing, and the limits and self-deceptions that are at the heart of all storytelling. As the story finds its way, through sea and desert, and the realms of mysticism and magic, we learn of a passionate, volatile relationship, one severely tested through countless separations, of Ayn's relationships with other men, including her intense encounters with a Cors.